Achilles Tendon Morphology Is Related to Triceps Surae Muscle Size and Peak Plantarflexion Torques During Walking in Young but Not Older Adults - Knaus, Katherine R.; Ebrahimi, Anahid; Martin, Jack A.; Loegering, Isaac F.; Thelen, Darryl G.; Blemker, Silvia S. (Frontiers in Sports and Active Living, 2020)
The interaction of the triceps surae muscles and the Achilles tendon is critical in producing the ankle plantarflexion torque required for human walking. Deficits in plantarflexor output are a hallmark of reduced mobility in older adults and are likely associated with changes in the triceps surae muscles that occur with age. Structural differences between young and older adults have been observed in the Achilles tendon and in the triceps surae muscles. However, less is known about how age-related differences in muscle and tendon morphology correspond with each other and, furthermore, how those morphology differences correlate with age-related deficits in function. The goal of this work was to investigate whether there is a correlation between age-related differences in triceps surae muscle size and Achilles tendon cross-sectional area (CSA) and whether either is predictive of ankle plantarflexion torque during walking. We used magnetic resonance imaging (MRI) to measure triceps surae muscle volumes and tendon CSAs in young (n = 14, age: 26 ± 4 years) and older (n = 7, age: 66 ± 5 years) adults, and we determined peak plantarflexion torques during treadmill walking. We found that individual muscle volumes as a percentage of the total triceps surae volume did not differ between young and older adults, though muscle volumes per body size (normalized by the product of height and mass) were smaller in older adults. Achilles tendon CSA was correlated with body size and muscle volumes in young adults but not in older adults. The ratio of tendon CSA to total triceps surae muscle volume was significantly greater in older adults. Peak ankle plantarflexion torque during walking correlated with body size and triceps surae volume in young and older adults but was correlated with tendon CSA only in the young adults. Structure–function relationships that seem to exist between the Achilles tendon and the triceps surae muscles in young adults are no longer evident in all older adults. Understanding mechanisms that determine altered Achilles tendon CSA in older adults may provide insight into age-related changes in function.